THE U.S. EXPERIENCE IN PLANNING AND MANAGING AGGLOMERATIONS AND ITS APPLICABILITY IN UZBEKISTAN (KIUT Publication, 2025)
This article analyzes the experience of planning and managing agglomerations in the United States and the prospects for applying these practices to the development of urban agglomerations in Uzbekistan. The main approaches, institutional structures, and financial mechanisms used in metropolitan planning and management in the U.S. were examined. Based on the U.S. experience, recommendations were developed for institutional, legal, and financial measures to effectively manage agglomerations in Uzbekistan. According to the research results, the development of urban agglomerations in Uzbekistan requires strengthening regional cooperation, enhancing the role of local government bodies, promoting public-private partnerships, and ensuring public participation in urban planning.